PENGARUH KEMAMPUAN DIRI, KOMITMEN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPILKABUPATEN ACEH BARAT - Sayid Priyakesuma; Naswan Efendi; Syarmadan Simamora; Riswan Halim Batubara; Rahmad Perdana Harianja (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2020)
The problems in research what is influence of self ability on performance. What is influence of organizational commitment on performance. What is influence of organization culture on performance. What is influence of self ability, organizational commitment and organization culture on performance. The research of purposes is for know and analysis influence of self ability on performance. For know and analysis influence of organizational commitment on performance. For know and analysis influence of organization culture on performance. For know and analysis influence of self ability, organizational commitment  and organization culture on performance. Samples in the  research amount to 32 employees people. Data analyze technique in the research using descriptive analyze and regression analize. The results of this research explain of self ability variable effect significant and positive on performance. Organizational commitment variable effect significant and positive on performance. Organization culture variable effect significant and positive on performance. Self ability, organization commitment and organization culture variable effect significant and positive on performance.